Pozícia ošetrovateľstva v podpore zdravia osôb so zdravotným postihnutím = Role of Nursing in the Support of Health in Persons with Disabilities - Gerlichová, Katarina; Matišáková, Iveta; Grabczak, Pavel (Vilnius: Mykolas Romeris Universitetas)
On a global scale, the last decade of the 20th century has been characterized by distinct social changes and the perception of disability in peoples' lives has admittedly been part of them. Disabled people create the largest minority in the world. The affected do not voluntarily select or choose the health handicap. The individual who became disabled, alternatively was born with a disability, has to come to terms with the consequences influencing his life, and not everyone can manage that on their own.
Keywords: zdrowie; niepełnosprawność; osoby niepełnosprawne; adaptacja; rodzina; pielęgniarstwo; health; disability; disabled; nursing; adaptation; family